Concluding Reflections on the Central and Eastern European Region and the European Court of Human Rights - Krajnyák, Enikő (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
This chapter offers concluding reflections on the evolving relationship between Central and Eastern European (CEE) states and the European Court of Human Rights (ECtHR). Drawing on the jurisprudence of the Strasbourg Court, it examines this relationship by exploring how cases originating from the region have influenced the development of the ECtHR’s jurisprudence, introducing new thematic concerns and doctrinal refinements. Through a synthesis of the jurisprudence of the Strasbourg Court, the chapter aims to identify common patterns and possible divergences in this mutual interaction and reflects the ECtHR’s dual role as both a transformative force in post-transition societies and a forum responsive to the region’s specific legal and social challenges.Keywords: European Court of Human Rights, Central and Eastern Europe, human rights, margin of appreciation